Treatment With Cladribine Selects IFNγ+IL17+ T Cells in RRMS Patients – An In Vitro Study - Dobreanu, Minodora; Manu, Doina Ramona; Mănescu, Ion Bogdan; Gabor, Manuela Rozalia; Huţanu, Adina; Bărcuţean, Laura; Bălaşa, Rodica (Frontiers in Immunology, 2021)
Background: Multiple sclerosis (MS) is an incurable autoimmune disease mediated by a heterogeneous T cell population (CD3+CD161+CXCR3−CCR6+IFNγ−IL17+, CD3+CXCR3+CCR6+IFNγ+IL17+, and CD3+CXCR3+IFNγ+IL17− phenotypes) that infiltrates the central nervous system, eliciting local inflammation, demyelination and neurodegeneration. Cladribine is a lymphocyte-depleting deoxyadenosine analogue recently introduced for MS therapy as a Disease Modifying Drug (DMD). Our aim was to establish a method for the early identification and prediction of cladribine responsiveness among MS patients. Methods: An experimental model was designed to study the cytotoxic and immunomodulatory effect of cladribine. T cell subsets of naïve relapsing-remitting MS (RRMS) patients were analyzed ex vivo and in vitro comparatively to healthy controls (HC). Surviving cells were stimulated with rh-interleukin-2 for up to 14days. Cell proliferation and immunophenotype changes were analyzed after maximal (phorbol myristate acetate/ ionomycin/ monensin) and physiological T-cell receptor (CD3/CD28) activation, using multiparametric flow cytometry and xMAP technology. Results: Ex vivo CD161+Th17 cells were increased in RRMS patients. Ex vivo to in vitro phenotype shifts included: decreased CD3+CCR6+ and CD3+CD161+ in all subjects and increased CD3+CXCR3+ in RRMS patients only; Th17.1 showed increased proliferation vs Th17 in all subjects; CD3+IL17+ and CD3+IFNγ+IL17+ continued to proliferate till day 14, CD3+IFNγ+ only till day 7. Regarding cladribine exposure: RRMS CD3+ cells were more resistant compared to HC; treated CD3+ cells proliferated continuously for up to 14 days, while untreated cells only up to 7 days; both HC/RRMS CD3+CXCR3+ populations increased from baseline till day 14; in RRMS patients vs HC, IL17 secretion from cladribine-treated cells increased significantly, in line with the observed proliferation of CD3+IL17+ and CD3+IFNγ+IL17+ cells; in both HC/RRMS, cladribine led to a significant increase in CD3+IFNγ+ cells at day 7 only, having no further effect at day14. IFNγ and IL17 secreted in culture media decreased significantly from ex vivo to in vitro. Conclusions: CD3+ subtypes showed different responsiveness due to selectivity of cladribine action, in most patients leading to in vitro survival/ proliferation of lymphocyte subsets known as pathogenic in MS. This in vitro experimental model is a promising tool for the prediction of individual responsiveness of MS patients to cladribine and other DMDs.